Peran Kepala Sekolah Sebagai Manajerial dalam Meningkatkan Mutu Berbasis Rapor Pendidikan di SMP Negeri 13 Kei Kecil - Laurensia Jamlean; Patris Rahabav; J. Papilaya; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Education report cards are part of the transformation of independent learning. Various independent learning policies are a transformation to create superior Indonesian human resources (HR) that have a Pancasila student profile with policies. This research aims to determine the role of school principals as managers in improving the quality of education report cards. This research uses a descriptive method with a qualitative approach. The subjects of this research are the principal, deputy principal and head of the literacy and numeracy program and the research object is the role of the principal as manager and educational report cards. Data collection used Interview, Rubric and Document Study methods. The research results show that if the school principal carries out managerial duties including planning, organizing, mobilizing and supervising optimally, there will be an increase in quality in the school.